Potential for increasing soil nutrient availability via soil organic matter Improvement using pseudo panel data - Chavez Clemente, Maria Daniela (2014)
Fixed and random effect models were applied to a pseudo-panel data built of soil analysis reports from tobacco farms to analyze relationships between soil characteristics like soil organic matter (SOM) and soil nitrogen (N), phosphorous (P) and potassium (K) and to explore the potential for improving nutrients availability by increasing SOM content. These econometric models may account for unobserved specific characteristics such as location-specific characteristics, management strategies, farmers’ skills and preferences and environmental heterogeneity. Positive relationships were found between N, P and K availability and SOM. The random effect model reports a highly significant elasticity of N with respect to SOM of 0.75, meaning that an increase of 1% of SOM will increase soil N by 0.75%. Using this elasticity, the required SOM improvement of green manure was calculated at which costs of green manure would exactly equal benefits in terms of reduced N fertilizer use. Costs and benefits are equal if the SOM increases from 1.55% to 3.61%, which is barely achieved according to the literature. Hence, growing green manure crops to increase SOM and thereby N availability is not economically attractive. However, additional benefits may arise from SOM improvement and growing green manure crops.